Evaluation of Three Swedish ICD-10 Primary Care Versions: Reliability and Ease of Use in Diagnostic Coding - Nilsson, G.; Petersson, H.; Åhlfeldt, H.; Strender, L.-E. (Methods of Information in Medicine, 2000)
If computer-stored information is to be useful for purposes other than patient care, reliability of the data is of utmost importance. In primary healthcare settings, however, it has been found to be poor. This paper presents a study on the influence of coding tools on reliability and user acceptance. Six general practitioners coded 152 medical problems each by means of three versions of ICD-10, one with a compositional structure. At code level the reliability was poor and was almost identical when the three versions were compared. At aggregated level the reliability was good and somewhat better in the compositional structure. Ideas for improved user acceptance arose, and the study explored the need for several different tools to retrieve diagnostic codes.
Keywords: Coding; ICD; Reliability; Family Medicine; Medical Modeling